Character and Civic Ed conference is April 12-13 - Uribes, Tom::::::::: (2013)
The 29th annual Conference on Character and Civic Education will be presented April 12 and 13 by Fresno State's Kremen School of Education and Human Resources and Bonner Center for Character Education.